Synovial Sarcoma of the Head and Neck: A Case of Predominantly Cystic Mass - Park, Ji Kang; Ham, Soo Youn; Hwang, Jae Cheol; Jeong, Yoong Ki; Lee, Jong Hwa; Yang, Seoung-Oh; Suh, Jae-Hee; Choi, Dae Hwa (American Journal of Neuroradiology, 2004)
Summary: We report a case of predominantly cystic synovial sarcoma partly adherent to the hyoid bone in the submental area. The mass demonstrated posterior acoustic enhancement at sonography and a complex cystic mass with mural nodules and solid septa at CT.